Hubungan Status Gizi Remaja Putri Dengan Siklus Menstruasi Di MTs Darun Najah Gading Dusun Sumber Kenanga Jatirejo Mojokerto - Agus Dwi Rahayu; Sulis Diana (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2019)
One of the risk factors of variability of the menstrual cycle is the nutritional status of young adolescents. Because the quality of nutrition and nutrition affect the performance of the hypothalamus gland which has a role to control the smoothness of the menstrual cycle there. The research objective was to determine the relationship with the nutritional status of young women in the menstrual cycle of MTs Darun Najah Gading Jatirejo Mojokerto. Research design is observational analytic study with cross sectional approach. The independent variable was the nutritional status of young adolescents and the dependent variable is the menstrual cycle. The population was all young adolescents class VII and VIII as many as 41 people, then the total sampling technique is taken entirely as a sample. Nutritional status were collected using a meter (meterline) and age data, while menstrual cycle data was taken using a questionnaire on December 4 to 9 June 2012. Furthermore, the data were processed and analyzed using the Chi square test. The results showed almost half of respondents have a short nutritional status of 20 respondents (48.8%) and the majority of respondents had normal menstrual cycles were 22 respondents (53.7%). Chi square statistical test results obtained Sig. (2 tailed) (0.033) <α (0.05) means H0 rejected and H1 accepted, meaning that there is a link the nutritional status of young adolescents with menstrual cycle in MTs Darun Najah Gading Jatirejo Mojokerto. Family socioeconomic status background of the nutritional status of young women to be short, but even under conditions that completely limited, parents are quite capable of maintaining a comfortable home atmosphere for children, so that respondents can experience a normal menstrual cycle. Conclusion of this study is that there is a correlation between nutritional status of young adolescents with the menstrual cycle in MTs Darun Najah Gading Jatirejo Mojokerto. Young adolescents are advised to increase their knowledge about good nutrition and balanced. Health professionals can work with a tutor Business School Health to provide counseling on nutrition and menstruation.